1987
DOI: 10.1104/pp.83.4.1014
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Photosynthesis and Conductance of Selected Triticum Species at Different Water Potentials

Abstract: Leaf ps exchange characteristics ofa desert annual (Triticum kotschyi [Boiss.j Bowden) appears to maintain a higher degree of relative stomatal opening at reduced water potentials than T. aestivum, it is not clear if this is the only factor involved in the control of photosynthesis (13). In this study, we report that stomata had an important role in causing the relatively high photosynthetic rates of T. kotschyi under well watered conditions, but under water deficits the mesophyll capacity for photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 7 publications
7
36
0
2
Order By: Relevance
“…The P 3 concentration proved optimum and produced maximum values for these attributes studied (Figures 2, 3 and 4). A higher transpiration rate recorded in phosphorus treated leaves of the plant could be expected as transpiration is known to depend on stomatal conductance (Johnson et al 1987;McMurtrie 1993). Since the stomatal conductance showed improvement in the phosphorus supplied plants, a significant increase in the rate of transpiration is obviously expected.…”
Section: Discussionmentioning
confidence: 94%
“…The P 3 concentration proved optimum and produced maximum values for these attributes studied (Figures 2, 3 and 4). A higher transpiration rate recorded in phosphorus treated leaves of the plant could be expected as transpiration is known to depend on stomatal conductance (Johnson et al 1987;McMurtrie 1993). Since the stomatal conductance showed improvement in the phosphorus supplied plants, a significant increase in the rate of transpiration is obviously expected.…”
Section: Discussionmentioning
confidence: 94%
“…1) are typcial for a long-term water stressed, but attached and recoverable leaf of a C3 species (14,17,29). Similar curves were obtained with D. lanata plants at different light intensities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the intercellular CO2 concentration (C*)' does not decrease to the CO2 compensation point, but remains high even during moderate stress in several species (14,17, 29), invalidates the hypothesis that only stomatal closure is responsible for the loss of net photosynthesis via CO2 depletion (13).…”
mentioning
confidence: 99%
“…They observed a linear decrease in photosynthesis when the leaf water potential declined to less than -1.1 MPa. Johnson et al (1987) investigated the photosynthesis response of Triticum species and found a curvilinear relationship between water potential and photosynthesis. Based on these observations it was concluded that the data showed the linear part of a curvilinear relationship, so the intercept data were not used as the maximum value of photosynthesis.…”
Section: Photosynthesis Decrease During Moisture Deficiencymentioning
confidence: 99%
“…Ghashghaie and Saugier (1989) provided valuable information about the photosynthesis and stomatal movement of tall fescue subjected to drought and different nitrogen levels at the same time. Johnson et al (1987) observed the photosynthesis and conductance of Triticum species over a soil drying cycle. Jones et al (1980) described the stomatal behaviour and morphological changes of perennial ryegrass subjected to slow and rapid rates of water stress.…”
Section: Introductionmentioning
confidence: 99%